Specificity in nitric oxide signalling - Umbreen, Saima (Journal of experimental botany, 2018)
Reactive nitrogen species (RNS) and their cognate redox signalling networks pervade almost all facets of plant growth, development, immunity, and environmental interactions. The emerging evidence implies that specificity in redox signalling is achieved by a multilayered molecular framework. This encompasses the production of redox cues in the locale of the given protein target and protein tertiary structures that convey the appropriate local chemical environment to support redox-based, post-translational modifications (PTMs). Nascent nitrosylases have also recently emerged that mediate the formation of redox-based PTMs. Reversal of these redox-based PTMs, rather than their formation, is also a major contributor of signalling specificity. In this context, the activities of S-nitrosoglutathione (GSNO) reductase and thioredoxin h5 (Trxh5) are a key feature. Redox signalling specificity is also conveyed by the unique chemistries of individual RNS which is overlaid on the structural constraints imposed by tertiary protein structure in gating access to given redox switches. Finally, the interactions between RNS and ROS (reactive oxygen species) can also indirectly establish signalling specificity through shaping the formation of appropriate redox cues. It is anticipated that some of these insights might function as primers to initiate their future translation into agricultural, horticultural, and industrial biological applications